Public-Private Partnership in infrastructure development: Case studies from Asia and Europe - Hans Wilhelm Alfen; Satyanarayana N. Kalidindi; Stephen Ogunlana; ShouQing Wang; Martinus P. Abednego; Andrea Frank-Jungbecker; Yu-Chien Amber Jan; Yongjian Ke; YuWen Liu; L. Boeing Singh; GuoFu Zhao (Verlag der Bauhaus-Universität, 2009)
Development of infrastructure projects with private engagement through PPP has become one of the commonly adopted procurement strategies in developed and developing countries. All over the world where PPP procurement has been used in one form or another, the way in which it is carried out has become an important issue. Yet, there is no standard method of PPP implementation as each country adapts the process as appropriate for its own culture, economy, political climate and legal system. It is therefore essential that all parties likely to be involved have a common understanding of the principles underlying PPP structures and an appreciation of the key issues from the standpoints of the private as well as the public sectors. PPP projects with substantial private investments involve participation of stakeholders with diverse perspectives, which can lead to different perceptions on the viability of the project. The introduction chapter covers the general issues of PPP implementation and presents an overview of the use of PPP in the delivery of public infrastructure and services across the world. Following, in five case studies PPP projects from Asia and Europe are presented and reveal differences in the respective approaches of each country. The case studies analyze project objectives, scope and site as well as legal, contractual and financial framework under which the projects were realized. Each case study closes with a chapter discussing the different approaches and summarizing lessons learned.
urn:nbn:de:gbv:27-20100922-160114-1
Keywords: 330; Fallstudien; Infrastrukturentwicklung; Konzession; Projektfinanzierung; Case Studies; Concession; Europe; Infrastructure Development; Project Finance